A cytochrome C electron transfer switch modulated by heme ligation and isomerization of a peptidyl‐prolyl bond1. Issue 1 (19th January 2013) - Bandi, Swati; Bowler, Bruce E.; Maran, Flavio; Toniolo, Claudio
Abstract Intermolecular electron transfer (ET) between hexaamineruthenium(II), a6Ru2+, and a K73H/K79A variant of iso‐1‐cytochrome c, iso‐1‐Cytc, is used to study conformational ET switches mediated by His73‐heme ligation and cis to trans isomerization of the Ile75‐Pro76 peptidyl‐prolyl bond of iso‐1‐Cytc. The biomolecular rate constant for ET to the native state of K73H/K79A iso‐1‐Cytc is ∼270 mM−1 s−1 near neutral pH. The unimolecular conformational ET switches due to His73‐heme ligation and the Ile75‐Pro76 peptidyl‐prolyl bond gate ET at rate constants of 5 to 10 s−1 and 0.05 to 0.06 s−1. Thus, at 1 mM a6Ru2+, these conformational ET switches slow electron transfer by about 50‐ and 5000‐fold, respectively. The conformational ET switches are populated between pH 5 and 7, providing a means of modulating ET in this redox protein over several orders of magnitude by simply changing pH. The conformationally‐gated ET measurements are analyzed in the context of previous pH jump measurements on the His73‐heme alkaline transition of K73H/K79A iso‐1‐Cytc. The ability to obtain microscopic rate constants with conformationally‐gated ET measurements has allowed more precise determination of the pKas of the three ionizable groups that mediate population of the His73‐heme ET switch. We have also been able to show that the ionizable group with a pKa near 9 stabilizes the His73‐heme conformer relative to the native state of iso‐1‐Cytc and that contrary to the conclusions from our pH jump studies, this ionization does not strongly affect the rate of the Ile75‐Pro76 peptidyl‐prolyl isomerization. © 2012 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 114–124, 2013.